Fossilization Type of Elephas hysudrindicus from Blora on the Basis of Petrographic and Scanning Electron Microscopic Analyses - Danny Z. Herman (Indonesian Journal on Geoscience, 2011)
DOI: 10.17014/ijog.v6i2.117Either fossils of the hominid or vertebrate have long been known from terraces along the Solo River in Central and East Java. Most terraces consist of andesitic sand to andesitic tuffaceous sand with either gravelpebble or conglomerate and some of them contain vertebrate fossils. It is in this place, an ancient elephant fossil named Elephas hysudrindicus was discovered in 2009. This fossil was discovered at an abandoned sand quarry of Sunggun area, Medalem Village, Kradenan Subregency, Blora Regency which and can be mentioned as a great event for the Geological Museum. It was said as a phenomenal discovery, because the fossil was found within the terrace with condition of nearly complete skeleton of an individual elephant. Some bone fragments of Elephas hysudrindicus fossil is treated as rock specimens because a number of minerals fill in either pore spaces or cavities or cracks within bones, and such infilling minerals can be observed in cut sections of the bones. Main goals of the study are to determine the distribution and type of minerals within the bones, interpret environment of deposition, and identify fossilization type. The methodology used in this study consists of petrographic and Scanning Electron Microscopic (SEM) analyses. Based on the petrographical observation, some bone specimens of Elephas hysudrindicus fossil are characterized by fibrous and porous feature with cracks occuring locally. Whilst, examination with SEM shows that the bone specimens are apparently composed of collophane or massive cryptocrystalline variety of apatite as the principal component of fossil bone, having physical characteristic of spheroidal structure and cavities of 100 to 1500 micron (μ) in diameter. Most cavities and pore spaces are predominantly filled in by either authigenic crystals of rhombohedral calcite and lesser pseudohexagonal kaolinite with either slightly minerals of manganese oxide or iron oxide or ilmenite, including oxidized kaolinite and calcium iron silicate. Impregnation during diagenesis may be the most appropriate expression for fossilization process of the Elephas hysudrindicus. It is indicated by the existing authigenic minerals within the bones cavities, pore spaces, and cracks which are possibly due to precipitation of mineralized fluids originated from groundwater within the terrace.